Research on Quality Evaluation of Friction Stir Welding and Identification of Tunnel Defect Characteristics Based on Acoustic Emission Signals - Mishra, Manu; Srivastava, Gaurav; Shaurya, Animek (Journal of Progress in Civil Engineering, 2025)
Friction stir welding (FSW) is a solid-state welding process that joins two pieces of material together without melting them. It heats the metals using the heat produced by friction between the stir head and the base metal. A non-consumable tool with a shoulder and pin rotates and is inserted between the two pieces of material. The tool's friction with the material generates heat, which softens the material near the tool. The tool then moves along the joint line, mixing the softened material to create a solid weld. Friction stir welding is typically used in applications where conventional welding methods do not provide adequate mechanical properties or a cost-effective process. FSW is used in the manufacture of EV components like battery cases, motor cases, and inverter cases. It can also be used to join cooling parts for semiconductor equipment [1]. In the present work, assessment of weld quality and characterization of tunnel defect was done by using different tool shoulder parameters like flat, concentric, concave, scroll shoulders by keeping conical threaded pin constant for all tools with Acoustic Emission set up. The research work aim is , assessment of weld quality of friction stir welds produced by different tool shoulder parameters by Acoustic Emission technique by conducting characterisation tests like tensile test for each samples produced by all tools. Characterization of tunnel defect was done by considering the X Ray radiographic results and measurement of size of defects. This has been done by considering the AE parameters with the intention to use in on-line monitoring of process. The results of AE and radiographic test along with tensile test, defects measurement confirms that the Acoustic Emission technique found feasible method for online monitoring, assessment of weld quality and characterization of defects [2].